Komodifikasi tenaga kerja dalam praktik gotong royong di masyarakat pedesaan - Alifio Adlin Enggarianto; Masrukin Masrukin; Ankarlina Pandu Primadata (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
The practice of mutual cooperation, traditionally aimed at strengthening community collectivity and affectivity, has undergone notable changes, particularly in the context of labor commodification within these practices. Based on this, this research aims to analyze the commodification of labor in mutual cooperation practices and the factors behind it. This research employs a qualitative approach with a case study method, utilizing purposive sampling for participant selection and in-depth interviews for data collection, while the analysis is conducted using the Miles and Huberman interactive model. The results reveal that the commodification of labor in mutual cooperation reflects a significant shift in reciprocal relationships, as theorized by George Caspar Homans' social exchange theory, which emphasizes the balance of expected rewards against incurred costs in social actions. Initially, rewards in mutual cooperation were viewed as social agreements that fostered community solidarity and emotional connection. However, this perspective has shifted, with mutual cooperation increasingly being treated as a material commodity. This change is largely attributed to societal unpreparedness in facing the social pressures of the Covid-19 pandemic and the resultant social jealousy caused by the unequal distribution of social assistance during the crisis. Remarkably, even after the pandemic, the trend of labor commodification in mutual cooperation continues, driven by persistent societal envy over the inequity of pandemic-related social assistance, highlighting the lasting impact of societal and economic pressures on traditional social practices.